Instrumen Kebhinekaan Global: Piranti Pengukuran Elemen Profil Pelajar Pancasila - Rosalia Dewi Nawantara; Nora Yuniar Setyaputri; Rozi Bintang Ambar Pratiwi (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2024)
Student Profile of Pancasila became the goal of character education promoted by the Ministry of Education Culture Research and Technology. Through the character education program is expected to emerge students who have global competence and behave in accordance with the values of Pancasila. One of the elements in Pancasila's student profile is a global self-reliance profile. Students who possess these traits have a passion for preserving a culture of integrity, locality and identity and are open-minded to other cultures. In order to realize these characteristics, it is necessary to understand the values of humility. So we need to develop an instrument to identify those profiles. This research is developmental research. This research will develop a global sensitivity questionnaire. The development of this questionnary uses the stages of Gregory. Data analysis uses descriptive and inferential statistics. The results of this study show that global sensitivity questionnaires are practically and theoretically acceptable.